The complete chloroplast genome of Codonopsis lanceolata (Campanulaceae). Issue 2 (3rd July 2018) - Lee, Junki; Kim, So-Yeon; Lim, Jong-Sung; Sook Chun, Hyang; Kwon, Kisung; Koh, Youngho; Kang, Tae Sun; Kang, Jung-Hwa; Kim, Eun-Jeong; Nah, Gyoungju
Abstract: The complete chloroplast genome sequence of Codonopsis lanceolata was determined by next generation sequencing. The total length of chloroplast genome of C. lanceolata was 169, 447 bp long, including a large single-copy (LSC) region of 85, 253 bp, a small single-copy (SSC) region of 8060 bp, and a pair of identical inverted repeat regions (IRs) of 38, 067 bp. A total of 110 genes was annotated, resulting in 79 protein-coding genes, 27 tRNA genes, and 4 rRNA genes. The phylogenetic analysis of C. lanceolata with related chloroplast genome sequences in this study provided the taxonomical relationship of C. lanceolata in the genus Campanula .